PANDANGAN ORIENTALIS TERHADAP QIRO’AT AL-QUR’AN - Hamnah Hamnah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Orientalist studies of qirâ'at are clearly an attempt to give Muslims doubts about the authenticity of the Ottoman manuscripts. Various orientalist views regarding qirâ'at, whether they are regarding the birth of various qirâ'at, then qirâ'at with meaning,as well as regarding qirâ'at with the Ottoman manuscripts are clearly filled with errors. The efforts made by the orientalists in destroying the authenticity of the Ottoman manuscripts still did not produce the results they had hoped for. Allah has guaranteed the authenticity of the Qur'an with all its aspects, therefore, orientalist efforts in destroying the belief of Muslims in the Qur'an will still be in vain.